Activity of Tissue Plasminogen Activator in Frozen Samples of Human Blood Plasma Euglobulin Fraction - Myroshnykov, Kyrylo V.; Shkrabak, Maria O.; Yatsenko, Tetiana A. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 187.